A high-fidelity human cervical muscle finite element model for motion and injury studies. Issue 4 (11th October 2021) - Li, Fan; Li, Honggeng; Lei, Kang; Zhang, Biao; Su, Sicheng; Hu, Wei; Cao, Yingchun; Nie, Jin
Abstract: Active muscle response is a key factor in the motion and injury of the human head and neck. Due to the limitations of experimentation and the shortcomings of previous finite element models, the influence of material parameters of cervical muscle on motions of the head and neck during a car crash have not been comprehensively investigated. In the present work, a model of the cervical muscle in a 50th-percentile adult male was constructed. The muscles were modelled using solid finite elements, with a nonlinear-elastic and viscoelastic material and a Hill material modelling the passive and active parts of each muscle, respectively. The head dynamic responses of the model were validated using results obtained from volunteer sled tests. The influence of the material parameters of a muscle on head and neck motions were determined. Our key finding was that the greater the stiffness and the contraction strength of the neck muscles, the smaller the rotation angle of the head and the neck, and, hence, the lower the risk of head and neck injury to occupants in a car crash.